ANALYSIS OF MARKETING MIX FACTORS AFFECTING THE PURCHASE DECISION OF HYBRID CORN SEEDS BISI-2 (Case Study in Pelem Village, Pare District, Kediri Regency) - Bahrul Alam (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
This study has some objections, for instance (1) to Analyze the correlation of marketing mix that consist of product, price, distribution, and promotion to purchasing decision of BISI-2 hybrid corn seed (2) to analyze marketing mix factors that consist of product factor, price factor, distribution factor, and promotion factor that affecting to farmer decision on purchase BISI-2 hybrid corn seed for once again in the next corn plant season or not. The location of study was purposively determined in Pelem Village, Pare Subdistrict, Kediri Regency with the consideration that area is center of corn cultivation. Sample total of this study is 105 respondents by accidental sampling method. The methods of analysis data in this study are descriptive analysis and quantitative analysis. Descriptive analysis used for describe the respondent answer of the question that given. The Quantitative analysis consist of Rank Spearman Correlation used for analyze the correlation of marketing mix to purchasing decision and Logistic Regression used for analyze marketing mix factors that affecting to farmer decision on purchase of BISI-2 hybrid corn seed for once again or not in the next corn cultivation. According to the result of analysis correlation marketing mix to the purchasing decision of BISI-2 hybrid corn seed by Rank Spearman Correlation shown all of the marketing mix factors consist of product, price, distribution, and promotion have a correlation to purchasing decision of BISI-2 hybrid corn seed. According to the result of analysis marketing mix factors that affecting to farmer decision on purchase of BISI-2 hybrid corn seed for once again or not in the next corn cultivation by Logistic Regression shown all of marketing mix factors consist of product, price, distribution,and promotion affecting to farmer decision on purchase of BISI-2 for once again or not, product factor has the higest effect on that farmer decision.